Impact of Skin Suture Pattern on Incision Perfusion Using Intraoperative Laser Angiography: A Randomized Clinical Trial of Patients With Ankle Fractures. Issue 10 (October 2020) - Shorten, Peter; Haimes, Mark; Nesbit, Robert; Bartlett, Craig; Schottel, Patrick
Abstract : Objectives: To assess which skin suture pattern—simple, vertical mattress, horizontal mattress, Allgöwer–Donati (AD), or running subcuticular—enables the greatest degree of perfusion as measured by indocyanine green laser angiography after ankle fracture surgery. Design: Prospective, randomized. Setting: Level 1 Academic Trauma Center. Patients/Participants: Seventy-five patients undergoing ankle fracture surgery were prospectively randomized to 1 of 5 skin suture patterns (n = 15 per cohort). Patient demographics and operative parameters were similar between groups. Main Outcome Measurements: Skin perfusion was assessed intraoperatively after skin closure using indocyanine green laser angiography and quantified in fluorescence units. Two perfusion values were collected: (1) mean incision perfusion was the mean of 10 points along the incision and (2) mean perfusion impairment was the perfusion difference between the incision and the skin adjacent to it. We also collected a postoperative patient scar assessment score. Results: Running subcuticular closure had significantly better mean incision perfusion than all other closure patterns. Mean perfusion impairment also favored running subcuticular closure, which was significantly lower than all other suture patterns except AD. We found no patient perceived cosmetic differences between the 5 suture pattern types. Conclusions: Running subcuticular suture pattern resulted in the greatest incision perfusion than simple, horizontal mattress, vertical mattress, and AD techniques after ankle fracture fixation. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.